Video Self-Modeling: A Promising Strategy for Noncompliant Children. (July 2014) - Axelrod, Michael I.; Bellini, Scott; Markoff, Kimberly
The current study investigated the effects of a Video Self-Modeling (VSM) intervention on the compliance and aggressive behavior of three children placed in a psychiatric hospital. Each participant viewed brief video clips of himself following simple adult instructions just prior to the school's morning session and the unit's afternoon free period. A multiple baseline design across settings was used to evaluate the effects of the VSM intervention on compliance with staff instructions and aggressive behavior on the hospital unit and in the hospital-based classroom. All three participants exhibited higher levels of compliance and fewer aggressive episodes during the intervention condition, and the effects were generally maintained when the intervention was withdrawn. Hospital staff reported at the conclusion of the study that the VSM intervention was easy to implement and beneficial for all participants. Taken altogether, the results suggest VSM is a promising, socially acceptable, and proactive intervention approach for improving the behavior of noncompliant children.